Avaliação dos efeitos da própolis nos parâmetros cardíacos e nos neurônios dopaminérgicos no modelo de parkinsonismo induzido pela 6-Hidroxidopamina - Goncalves, Valeria De Cassia [UNIFESP] (2019)
Parkinson's disease (PD) is the second most common neurodegenerative disease in the elderly after Alzheimer's disease. Clinically manifested by classic motor symptoms, which appear after 50-60% loss of dopaminergic cells in the nigrostriatal pathway, PD is a multisystem disorder that causes several nonmotor symptoms that may appear before the onset of motor deficits. Cardiovascular changes are among the most common non-motor symptoms in PD that result in reduced quality of life and even death of the patient. There are few studies on animal models of PD to understand the pathological association between the disease and cardiovascular abnormalities. This study investigated the effects of Brazilian green propolis on cardiovascular parameters represented by heart rate (HR) and heart rate variability (HRV) and on dopaminergic neuron death in the model of PD induced by bilateral injection of 6-hydroxidopamine (6-OHDA) (12µl / µg) in the striatum of Wistar rats. Propolis was administered by gavage for 40 days after 6-OHDA injection. Four groups of animals were studied: (1) rats submitted to stereotactic surgery that did not receive the neurotoxin injection and received water via oral gavage (sham); (2) rats submitted to stereotactic surgery that did not receive the neurotoxin injection and received propolis via oral gavage (sham propolis); (3) rats submitted to the 6-OHDA model and received water via oral gavage; and (4) rats submitted to the 6-OHDA model and received propolis via oral gavage. Reductions in HR and HRV were detected in parkinsonian animals compared to the other groups and propolis resulted in an increase of these parameters in parkinsonian animals that received this natural compound compared to parkinsonian animals that received water, suggesting a cardioprotective role of propolis. In the parkinsonian rats, propolis attenuated dopaminergic neuron death in the substantia nigra compacta (SNpc) and reduced striatal fiber degeneration, suggesting a neuroprotective action detected by positive immunoreactivity to tyrosine hydroxylase. Parkinsonian animals receiving propolis showed a significant weight gain compared to parkinsonian rats receiving water. These findings point to the beneficial effects of propolis on cardioprotection, neuroprotection and weight modulation in parkinsonism induced by the 6-OHDA model and suggest the therapeutic potential of Brazilian green propolis in the search for disease-modifying approaches.